Reaktualisasi Nilai Kearifan Lokal Kepemimpinan Melayu untuk Mewujudkan Sistem Politik yang Demokratis dan Bermartabat - Anshori, Muhamad Zakwan; Rahmi, Ayu Atika; Nurrahmawati, Siska Dyah (Lembaga Kajian, Penelitian dan Pengembangan Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Local wisdom in leadership is a local genius spirit that has the meaning that with knowledge, cleverness, wisdom in making decisions by deepening the tradition that has been embedded in the culture as a representation of the existing problems. This study illustrates a re-actualization of the local wisdom of Malay leadership to create a democratic and dignified political system in Indonesia and to address the endless problems of the political system in Indonesia. Excavation of local wisdom values Malay leadership is expected to be a solution to overcome the dynamics of society with a high level of plurality by giving the character not just promise , giving priority to common interests rather than personal interests, giving exemplary, faithful life in the strengthening of legal and potlitical culture for the realization of constitutional values in accordance with the ideals of Indonesian democracy. Kearifan lokal dalam kepemimpinan merupakan spirit local genius yang memiliki makna bahwa dengan pengetahun, kepandaian dan kebijaksanaan dalam mengambil keputusan dengan mendalami tradisi yang telah tertanam dalam budaya tersebut sebagai representasi dari permasalahan yang ada.Penulisan ini menggambarkan tentang sebuah pengaktualisasian kembali nilai kearifan lokal kepemimpinan Melayu untuk mewujudkan sistem politik yang demokratis dan bermartabat di Indonesia serta untuk menjawab permasalahan sistem politik di Indonesia yang tidak ada habisnya. Penggalian nilai-nilai kearifan lokal kepemimpinan Melayu diharapkan dapat menjadi solusi untuk mengatasi dinamika masyarakat dengan tingkat pluralitas yang tinggi dengan memberikan karakter yang tidak sekedar mengumbar janji, mementingkan kepentingan bersama daripada kepentingan pribadi, memberikan keteladanan, kehidupan yang beriman dalam penguatan budaya hukum dan politik demi terwujudnya nilai-nilai konstitusi sesuai dengan cita-cita demokrasi bangsa Indonesia.